(untitled) (International Journal of Food and Nutritional Sciences, 2022)
"The problem with gender is that it prescribes how we should be rather than recognizing how we are. Imagine how much happier we would be, how much freer to be our true individual selves, if we didn’t weigh gender expectations."(Adichie, 2014). In contemporary times, hyper-independence and anti-feminism have been marked as major features of masculine gender. The gender expectations have led the men to be excessively violent, aggressive and discriminatory against all the other genders. The stigma of toxic masculinity has been attached and feared. Masculinity is a wide and complex concept, and cannot be contained in the traditional, culture-specific sphere for long. The negative reverberations of traditional masculinity have culminated in the term- Toxic Masculinity. This research paper attempts to study the aspects of Toxic Masculinity as presented in the poems- First Light by Chen Chen and Duplex By Jericho Brown. The next two poems - Coniferous Fathers by Michael Kleber Diggs and If by Rudyard Kipling throw light on the kind of masculinity and fatherhood we need to facilitate the positive masculinity that is inclusive and gentle. The poems have been briefly analysed. The paper distinguishes the language and conventions that frame men and masculinities and provides an insight into the conflicts of the changing nature of masculinities through the stated poems.